2010
DOI: 10.1590/s0102-09352010000300033
|View full text |Cite
|
Sign up to set email alerts
|

Estimação por aproximação química dos teores de proteína indegradável insolúvel em detergente neutro em forragens tropicais

Abstract: Estimação por aproximação química dos teores de proteína indegradável insolúvel em detergente neutro em forragens tropicais [Estimation of undegradable neutral detergent insoluble protein in tropical forages by chemical approaching]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Therefore, this approach must be utilized with caution, and it is preferable, when feasible, that the estimate of the UNDIP be obtained by biological method, i.e., through the evaluation of the residual CP of the iNDF estimated by long-term in situ procedures, followed by treatment of the sample with neutral detergent fiber for the removal of microbial debris (Clipes et al, 2010a;Detmann et al, 2010b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this approach must be utilized with caution, and it is preferable, when feasible, that the estimate of the UNDIP be obtained by biological method, i.e., through the evaluation of the residual CP of the iNDF estimated by long-term in situ procedures, followed by treatment of the sample with neutral detergent fiber for the removal of microbial debris (Clipes et al, 2010a;Detmann et al, 2010b).…”
Section: Resultsmentioning
confidence: 99%
“…According to Gomes et al (2011), none of the different methods employed at the evaluation of lignin fully meets the nutritional expectation, with significant differences in the results obtained in laboratories for all the methods applied. Stronger correlations between lignin contents and extent of the rumen degradation of the NDF have been obtained by methods distinct from the one adopted by the NRC (2001) and suggested by Detmann et al (2010a) (Traxler et al, 1998;Clipes et al, 2010b;Gomes et al, 2011). This seems to indicate that limitations intrinsic of the lignin content estimated by the method of acid hydrolysis may reduce the accuracy of estimates of the pdNDF and iNDF fractions by chemical approach.…”
Section: Resultsmentioning
confidence: 99%
“…However, as pointed out previously, such an analytic approximation can be a hindrance in some situations, because fistulated animals may not be available. Thus, an alternative equation was developed to obtain the UNDIP value from the acid detergent insoluble protein (ADIP) using data from feeds produced under tropical conditions (Detmann et al, 2010a;n = 540), that is given by:…”
Section: Sub-model For Cpmentioning
confidence: 99%
“…Due to this limitation, new sub-models to predict the digestible fractions of CP, EE, NFC, and NDF were developed and evaluated under tropical conditions (Detmann et al, 2004a;2006a;2006b;2006c;2008b;2008c;2010a). The unified assessment of these sub-models, that constitutes a new summative system, showed that they are capable of more exact prediction of the TDN content in diets offered to cattle in Brazil (Detmann et al, 2008b;Magalhães et al, 2010;Azevêdo et al, 2011;Sampaio et al, 2012), creating an alternative to applying the model adopted by the NRC (2001) and culminating in the adoption of the prediction system in the second edition of the BR-CORTE System (Detmann et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of crude fiber, the foods are first submitted to digestion with diluted acid and then to digestion with diluted base (alkali). The remaining portion after the two digests is named crude fiber, then considered as the portion of the indigestible carbohydrates by the animal (Detmann et al 2010;Silva and Queiroz, 2002). As the majority of fiber sources consumed by the animals are from a vegetable source, the definition of crude fiber basically covers the fibers of vegetal origin: cellulose and alkali-insoluble lignin (Silva and Queiroz, 2002).…”
Section: Apparent Digestibility Coefficientmentioning
confidence: 99%